Paronomasia in Humorous Discourse on Instagram @Queteryo: A Syntagmatic Perspective - Herlin Triana; Vivi Indriyani; Zaiton Binti Zakarya (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The development of digital communication has made humor a medium of linguistic expression that not only serves as entertainment, but also as a means of identity formation and social relationship management in virtual spaces. This study aims to reveal the forms, patterns of occurrence, and functions of paronomasia in digital humor discourse on Instagram using an integrated syntagmatic approach. The focus is on how wordplay and language forms are used to convey humorous meaning while building social interaction among social media users. This study uses a qualitative descriptive method. The data consists of humorous posts on the Instagram account @Queteryo published during the period from January to March 2024. Data collection was carried out through documentation and purposive sampling techniques, then analyzed in terms of discourse by combining syntactic, semantic, and pragmatic studies to identify paronomasia patterns and their communicative functions. The results of the analysis show that paronomasia in digital humor most often appears in imperative and declarative sentence structures by utilizing similarities in sound and word form. Pragmatically, paronomasia functions as a means of conveying satire, persuasive appeals, and indirect criticism that can increase audience engagement. The uniqueness of this study lies in the application of an integrated syntagmatic framework that provides new insights into linguistic creativity, the strengthening of digital literacy, and communicative awareness, especially for the younger generation.